Development of ZEP Quiz-Assisted Interactive Learning Media to Enhance Elementary Students' Spatial Literacy in Learning Cubes and Cuboids - Anisah Raniyah Mumtazah Mumtazah; Nurafni (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Spatial literacy is a fundamental competency that enables students to visualize, interpret, and communicate three-dimensional objects in mathematics learning. However, elementary geometry instruction continues to rely heavily on conventional teaching approaches, limiting students' opportunities to develop these essential skills through meaningful interaction. This study aimed to develop and evaluate ZEP Quiz-assisted interactive learning media to enhance elementary students' spatial literacy in learning cubes and cuboids. A Research and Development approach employing the ADDIE model was adopted to design, validate, implement, and evaluate the learning media. The study involved 57 fifth-grade students from an elementary school in East Jakarta, Indonesia, who participated in sequential small-group (n = 28) and large-group (n = 29) trials. Data were collected using a spatial literacy achievement test administered before and after the intervention and analyzed through descriptive statistics, Shapiro–Wilk and Levene's tests, paired-samples t-tests, and normalized gain (N-Gain) analysis using IBM SPSS Statistics. The findings revealed significant improvements in students' spatial literacy following the implementation of the developed media (p < 0.001). The average N-Gain scores reached 0.64 in the small-group trial and 0.70 in the large-group trial, indicating a moderate level of learning improvement. These findings demonstrate that ZEP Quiz-assisted interactive learning media provides an effective and engaging strategy for strengthening spatial literacy in elementary geometry learning while supporting the implementation of student-centered digital instruction.